Priorities for the minority? Street-based sex work and Partnerships and Communities Together (PACT) - Tracey Sagar (Criminology and Criminal Justice, 2012)
The article draws on empirical research carried over an eight month period where the authors observed PACT meetings in two suburbs of Cardiff. It focuses on local police/community consultation via PACT in the context of street based sex work and argues that priorities at PACT represent the views and opinions of a small community minority. Conversley, the article also draws on a public opinion survey carried out in the same two suburbs to illustrate how the wider community are more tolerant of street based sex work and highlights the views and opinions of the 205 residents who took part in the research with regard to community solutions to the problems presented by street based work.